Legal Protection of Women as Victims of Sexual Violence in Madadan Tana Toraja - Ristia Desmonda Amelinda; Gayatri Dyah Suprobowati (Universitas Sebelas Maret, 2025)
This research aims to find out and analyze how women are protected as victims of sexual violence in Madandan Tana Toraja. This is on the one hand because most victims of crimes against women, besides acts of violence, are sexual acts starting from acts of harassment (sexual harassment) to acts of sexual violence in the form of rape. Violence is any unlawful act with or without the use of physical and psychological means that poses a danger to life or body or results in the deprivation of a person's freedom. The Law No. 12 of 2022 Criminal Act of Sexual Violence (UU TPKS) as a whole reflects a progressive approach to dealing with sexual violence in Indonesia and is a significant step forward in efforts to prevent and handle sexual violence. This research is legal research, which examines it from a legal perspective using a normative juridical approach because the problem studied is closely related to law in books. Normative legal research is library research, namely research conducted from secondary data. The results of this research show that efforts to protect women as victims of sexual violence in Madandan Tana Toraja include each village having different traditional councils and rules regarding sexual violence. In fact, in this community, there is the highest customary sanction